Rural Leaders, Rural Places: Problem, Privilege, and Possibility - Kathleen Budge (Journal of Research in Rural Education, 2006)
I present a case study of the influence of rurality and a sense of place on leaders' beliefs about purposes of local schooling and their concomitant theories of action in one rural school district. Interview data show that despite their portrayal of life in the valley as a privilege, most leaders viewed their place as presenting more problems than possibilities in the lives of most students. I conclude with the suggestion that a critical leadership of place may best address the strengths and challenges found in much of rural America.